2022
DOI: 10.3389/fendo.2022.1068061
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targets in acromegaly

Abstract: Molecular therapeutic targets in growth hormone (GH)-secreting adenomas range from well-characterized surface receptors that recognize approved drugs, to surface and intracellular markers that are potential candidates for new drug development. Currently available medical therapies for patients with acromegaly bind to somatostatin receptors, GH receptor, or dopamine receptors, and lead to attainment of disease control in most patients. The degree of control is variable: however, correlates with both disease agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 86 publications
2
4
0
1
Order By: Relevance
“…12,13 Of note, the Nrg4 receptor ErbB4 is expressed in pituitary lacto-somatotroph cells. 14 We also found the high expression of adipokines Nrg4 in the human pituitary PRL cells in our study. Additionally, studies have revealed that in rat pituitary tumor cells, EGF exerts a promoting effect on the synthesis of PRL.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…12,13 Of note, the Nrg4 receptor ErbB4 is expressed in pituitary lacto-somatotroph cells. 14 We also found the high expression of adipokines Nrg4 in the human pituitary PRL cells in our study. Additionally, studies have revealed that in rat pituitary tumor cells, EGF exerts a promoting effect on the synthesis of PRL.…”
Section: Introductionsupporting
confidence: 78%
“…The N‐terminal EGF‐like polypeptide segment of Nrg4, with a molecular weight of 14 kDa, has been demonstrated to possess the ability to traverse the blood‐brain barrier 12,13 . Of note, the Nrg4 receptor ErbB4 is expressed in pituitary lacto‐somatotroph cells 14 . We also found the high expression of adipokines Nrg4 in the human pituitary PRL cells in our study.…”
Section: Introductionsupporting
confidence: 70%
“…The Pituitary Gland -An Overview of Pathophysiology and Current Management Techniques humoral, imaging and pathomorphological predictors for preliminary stratification of clinically homogeneous patients with a clear clinical prognosis and response to treatment [16,17].…”
Section: Tumor-oriented Diagnosis and Treatmentmentioning
confidence: 99%
“…The changes in ion permeability resulting from the activation of the receptor lead to a critical decrease in the intracellular concentration of calcium ions and cAMP, which blocks the secretion of GH and the proliferation of somatotrophs. Activation of SSTRs and specific proteins involved in intracellular signal transmission (AIP, ZAC1, RKIP, E-cadherin, β-arrestin) promotes suppression of GH secretion, inhibition of proliferation, cell migration and angiogenesis [16,19,37].…”
Section: Predictors Of Sensitivity To Somatostatin Receptor Ligandsmentioning
confidence: 99%
See 1 more Smart Citation